Synthesis and biological evaluation of Doxorubicin-containing conjugate targeting PSMA. Issue 10 (15th May 2019) - Ivanenkov, Yan A.; Machulkin, Alexey E.; Garanina, Anastasia S.; Skvortsov, Dmitry A.; Uspenskaya, Anastasia A.; Deyneka, Ekaterina V.; Trofimenko, Alexander V.; Beloglazkina, Elena K.; Zyk, Nikolay V.; Koteliansky, Victor E; Bezrukov, Dmitry S.; Aladinskaya, Anastasia V.; et al.
Graphical abstract: Abstract: Prostate-specific membrane antigen (PSMA), also known as glutamate carboxypeptidase II (GCPII), has recently emerged as a prominent biomarker of prostate cancer (PC) and as an attractive protein trap for drug targeting. At the present time, several drugs and molecular diagnostic tools conjugated with selective PSMA ligands are actively evaluated in different preclinical and clinical trials. In the current work, we discuss design, synthesis and a preliminary biological evaluation of PSMA-specific small-molecule carrier equipped by Doxorubicin (Dox). We have introduced an unstable azo-linker between Dox and the carrier hence the designed compound does release the active substance inside cancer cells thereby providing a relatively high Dox concentration in nuclei and a relevant cytotoxic effect. In contrast, we have also synthesized a similar conjugate with a stable amide linker and it did not release the drug at all. This compound was predominantly accumulated in cytoplasm and did not cause cell death. Preliminary in vivo evaluation has showed good efficiency for the degradable conjugate against PC3-PIP(PSMA + )-containing xenograft mine. Thus, we have demonstrated that the conjugate can be used as a template to design novel analogues with improved targeting, anticancer activity and lower rate of potential side effects. 3D molecular docking study has also been performed to elucidate the underlying mechanism of binding and to further optimization of the linker area for improving the target affinity.